P2 2 Taylor’s Turnstile Turbines: The Swiftie Solution - Brough, Oliver J. T.; Gardiner, Corban C. B.; Grout, Joel E.; Halliday, Tom E. (Physics Special Topics, 2023)
We investigate the total of the CO2 emission produced by private jets taken by Taylor Swift across her 2023 US Eras tour.This totalled 52.3 thousand kg of CO2 which is equivalent to 6.20 GW of power. Additionally, we explored the implementation of wind turbine-like turnstiles across this tour to see how much power could be generated back by her fans. We found that with 1.96 million people only 540 kW would be generated, equating to 0.00872% of the power used for private jet travel.